Gender- and age-related differences in the quality of mental health care among inpatients with unipolar depression: a nationwide study. (2nd November 2020) - Rasmussen, Line Ryberg; Videbech, Poul; Mainz, Jan; Johnsen, Søren Paaske
Abstract: Objective: The relationship between gender, age and the quality of mental health care among inpatients with depression is unclear. This study examined gender- and age-related differences in the quality of care as reflected by the fulfilment of process performance measures of care among inpatients with unipolar depression in Denmark. Methods: In a nationwide cohort study, 16, 858 patients admitted to psychiatric hospital wards for depression between 2011 and 2016 were identified from the Danish Depression Database. Patients were divided according to age (18–39, 40–65, 66–79 and ≥80 years) and stratified by gender. Quality of care was defined as having fulfilled process performance measures of care, reflecting national clinical guideline recommendations. High overall quality of care was defined as having received ≥80% of the processes. The associations were assessed using binomial regressions. Results: With men in the age group 18–39 years serving as the reference, men and women in the age category ≥80 years were more likely to receive higher quality of care with an adjusted relative risk (aRR) of 1.43 [95% confidence interval (CI) = 0.98; 2.10] and 1.30 (95% CI = 0.90; 1.90), respectively. Likewise, for men and women aged 66–79 years, the aRRs as 1.34 (95% CI = 1.07; 1.67) and 1.47 (95% CI = 1.14; 1.90). For men and women aged 40–65, the aRRs was 1.15 (95% CI = 1.00; 1.33) and 1.07 (95% CI = 0.93; 1.24), respectively. Conclusion: Older patients received higher quality of inpatient care for depression, as reflected by a higher proportion of fulfilled guideline supported process measures. In contrast, we found no gender-related differences.